2018
DOI: 10.30918/bbr.61.17.022
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiles of pathogen-challenged mulberry silkworm, Bombyx mori L. as a tool for disease diagnosis

Abstract: Metabolic profiles were detected in healthy and flacherie (inoculated with Bacillus sp.) and grasserie (inoculated with polyhedral bodies)-diseased Bombyx mori larvae. Free amino acids were separated and quantitatively determined by using hydrolysis method. Further, nitrogen (N) percentage was estimated with micro-Kieldahl method. Whereas, phosphor-molybdate method was applied for phosphorus (P) analysis. Results revealed that distinct differences in the amounts of eighteen individual amino acids in healthy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…Double cocoons occur when two silkworms spin the silk together, it occurs when temperature is high, in this research majority of double cocoons were observed in L5, this is due to high temperatures recorded in L5 which causes the mature worms to crowd thereby resulting to the spinning of cocoons together, this agrees with Taha et al (2014) [23] . Inside stained cocoon occurs when the pupa dies inside the cocoon causing stain, it occurs when the temperatures become low causing longer larval duration making the worm to be susceptible to diseases thus death, this could explain the phenomenon of highest percentage recorded in L2, where the temperatures were the lowest compared to other structurers.…”
Section: Cocoon Qualitysupporting
confidence: 89%
“…Double cocoons occur when two silkworms spin the silk together, it occurs when temperature is high, in this research majority of double cocoons were observed in L5, this is due to high temperatures recorded in L5 which causes the mature worms to crowd thereby resulting to the spinning of cocoons together, this agrees with Taha et al (2014) [23] . Inside stained cocoon occurs when the pupa dies inside the cocoon causing stain, it occurs when the temperatures become low causing longer larval duration making the worm to be susceptible to diseases thus death, this could explain the phenomenon of highest percentage recorded in L2, where the temperatures were the lowest compared to other structurers.…”
Section: Cocoon Qualitysupporting
confidence: 89%